2009
DOI: 10.1136/bjo.2009.158279
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in optic nerve head and retinal nerve fibre layer thickness parameters in children

Abstract: Compared with European Caucasian children, East Asian children generally had thicker RNFL and larger mean cup/disc ratios. Given the relatively lower prevalence of open angle glaucoma in Asians, these anatomical variations could contribute to better understanding of apparent racial differences in glaucoma susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 25 publications
4
39
2
Order By: Relevance
“…It is noticeable that a marked variation in pediatric RNFL thickness was consistently observed in studies using different versions of OCT. Several studies [5,16,17] reveal that OCT findings on the RNFL distributions in normal subjects also follow the ''ISNT rule,'' which states that normal optic discs display a distinctive configuration for disc rim thickness of inferior C superior C nasal C temporal [18]. Although the ISNT rule is helpful in detecting early glaucomatous optic neuropathy [19], the violation of this characteristic pattern of the RNFL distribution (superior inversely thicker rather than inferior, and/or temporal inversely thicker than nasal) in normal children was seen in our study and in others using Stratus OCT [3,5,6,8,10]. Besides, recent comparison studies of different OCTs [12,14] disclosed that the distribution pattern of RNFL in normal subjects was not consistent across measurements using different SD-OCTs and Stratus OCT.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…It is noticeable that a marked variation in pediatric RNFL thickness was consistently observed in studies using different versions of OCT. Several studies [5,16,17] reveal that OCT findings on the RNFL distributions in normal subjects also follow the ''ISNT rule,'' which states that normal optic discs display a distinctive configuration for disc rim thickness of inferior C superior C nasal C temporal [18]. Although the ISNT rule is helpful in detecting early glaucomatous optic neuropathy [19], the violation of this characteristic pattern of the RNFL distribution (superior inversely thicker rather than inferior, and/or temporal inversely thicker than nasal) in normal children was seen in our study and in others using Stratus OCT [3,5,6,8,10]. Besides, recent comparison studies of different OCTs [12,14] disclosed that the distribution pattern of RNFL in normal subjects was not consistent across measurements using different SD-OCTs and Stratus OCT.…”
Section: Discussioncontrasting
confidence: 42%
“…With the increasing use of SD-OCT, it is useful to compare our results with the reported values of RNFL thickness measured by the most popular TD-OCT device, the Stratus OCT (Carl Zeiss Meditec, Dublin, CA, USA), in normal children (Table 5) [3][4][5][6][7][8][9][10]. Seibold et al [14] found that average RNFL thicknesses measured with RTVue-100 OCT were significantly higher than those obtained with the Stratus OCT.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Also in the SMS, using time domain OCT, we reported that at both 6 and 12 years of age, East Asian children had larger CDRs compared with white children. 8 We found that increasing AL and more myopic refraction was associated with thinner average RNFL. This is in agreement with previous Cirrus HD-OCT studies, 6,39 as well as in a study using the Spectralis HRA þ OCT. 26 Studies using the time domain Stratus OCT instrument also reported thinner RNFL with increasing AL or myopic refraction.…”
Section: Eyementioning
confidence: 70%
“…Ethnic differences in RNFL thickness were previously reported with older time domain OCT. [6][7][8] The thinner nasal RNFL in East Asians could be explained by the greater prevalence of myopia in this population, which may be associated with a temporal shift in the arcuate nerve fiber bundles. 17 In a study by Knight et al, 16 the European/white sample had an average RNFL of 90.1 mm (SE 0.8) and their Chinese/East Asian sample had average RNFL of 96.4 mm (SE 1.1), compared with our values of 99.5±9.8 mm and 100.1±9.4 mm for these two groups, respectively.…”
Section: Eyementioning
confidence: 99%